Implementasi Metode Multi-Objective Optimization on the Basic of Ratio Analysis (Moora) dalam Menentukan Penilaian Kinerja Guru pada Sekolah Menengah Atas - Nur Rifkah Rusdianto; Khaidir Rahman Nasir; Nuraida Latif (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the assessment of teacher performance using a decision support system and to implement the Multi-Objective Optimization Method On The Basic Of Ratio Analysis (MOORA), in completing teacher performance assessments in high schools. This data was obtained through field tests and literature. The process of direct data collection in the form of interviews and documentation. The system development method used in this research is the Rapid Application Development (RAD) method. The RAD method is a system development method with a relatively short processing time. The results of the research from the implementation of the MOORA method in determining the performance assessment of high school teachers can be applied with the results of the questionnaire assessment of 81.54% or including very good.